The Perception of Organic Chemistry Students on the Use of the Socrative as an Active Learning - Maria Hosana Conceição (2021)
In the last year, with the global public health crisis, due to the Covid-19 pandemic, face-to-face education gave way to the use of technological platforms for online classes. Thus, the University of Brasilia (UnB) prepared its teaching staff for remote teaching, offering courses on the Moodle Aprender 3 and Office 365 platforms from Microsoft. On the other hand, the planning of the classes, in the remote mode, demanded from each teacher, a didactic sequence, logical, for the participation of the students, both in the synchronous classes, as in the asynchronous activities. Thus, the main objective of this study was to know the perception of Pharmacy students on the use of the Socrative platform, in the synchronous classes of the discipline of Organic Chemistry. It deals with an online platform in which students practice the content worked in the classroom using their smartphones or tablets. The study had the participation of sixty students from the second semester of the Pharmacy course, of the discipline of Organic Chemistry, offered in the 1st semester of 2020 who carried out the evaluations on the IUPAC nomenclature of organic compounds. Of the 40 students who answered the questionnaire, only 34 responses were considered in the content analysis, using the IRAMUTEQ software. The study proved to be promising for the use of Socrative in the categories of advantages, “difficulties”, suggestions and contributions